Answer:
Step-by-step explanation:
a) 3x^2-12x-11=3*x^2-3*2*2*x+3*4-23=3*(x^2-2*2x+2^2)-23=3*(x-2)^2-23
so a= -2 ,b= -23
b) x1=[12+V(12^2-4*3* -11)]/6=12/6+V(144+132)/6=2+2/6V69=2+1/3V69=
2+V69/9=2+V23/3
c=2, d= 23/3
Assume that the bank balance started at zero. Enter the income and outgo in chronological order: $300 - $50 - $75 + $225
Find the sum. This sum will represent the amount left in the account after the $225 deposit:
$250 - $75 + $225, or
$175 + $225 = $400 The final balance will be $400.
Pick 2 pairs of equations t<span>hen use addition and subtraction to eliminate </span>the same variable<span> from both pairs of equations then it is left with 2 variables
</span>Pick two pairs
<span><span>4x - 3y + z = - 10</span><span>2x + y + 3z = 0
</span></span>eliminate the same variable from each system
<span><span>4x - 3y + z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>4x - 3y + z = - 10</span>
<span>-4x - 2y - 6z = 0</span>
<span>-5y - 5z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>- x + 2y - 5z = 17</span>
<span>2x + y + 3z = 0</span>
<span>-2x + 4y - 10z = 34</span>
<span>5y - 7z = 34
</span></span>Solve the system of the two new equations:
<span><span>-5y - 5z = - 10</span>
<span>5y - 7z = 34</span>
<span>-12z = 24</span>
which is , <span>z = - 2</span>
<span>-5y - 5(- 2) = - 10</span>
<span>-5y = - 20</span>
wich is , <span>y = 4
</span></span>substitute into one of the original equations
<span>- x + 2y - 5z = 17</span>
<span>- x + 2(4) - 5(- 2) = 17</span>
<span>- x + 18 = 17</span>
<span>- x = - 1</span>
<span>x = 1</span>
<span>which is , </span><span>(x, y, z) = (1, 4, - 2)</span><span>
</span>Does 2(1) + 4 + 3(- 2) = 0<span> ? Yes</span><span>
</span>
Answer:
$324,870.00
Step-by-step explanation:
357,000.00 x .09 = $32,130.00
357,000.00 - $$32,130.00 = $324,870.00